FORMATION OF SILICA-SURFACTANT MESOPHASES STUDIED BY REAL-TIME IN-SITU X-RAY-POWDER DIFFRACTION - Obrien, S; Francis, R; Price, S; Ohare, D; Clark, S; Okazaki, N; Kuroda, K (1995)
Real-time in situ energy dispersive synchrotron X-ray powder diffraction data provides evidence for the formation of an intermediate lamellar silica-surfactant intercalate during the synthesis of the hexagonal mesophase derived from the layered polysilicate kanemite, whereas no intermediate phases are observed during the formation of the silica-surfactant mesophase that leads to the mesoporous material MCM-41.